The effect of excellent service and public satisfaction on employee performance in the process of making E-KTP: Pengaruh Pelayanan Prima Dan Kepuasan Masyarakat Terhadap Kinerja Pegawai Dalam Proses Pembuatan E-KTP - Kelik Purwanto; Nesi Pitria Ningsih; Mayroza Wiska (International Journal of Management and Business (IJMB), 2020)
The purpose of this study was to determine how the effect excellent service and community satisfaction partially and simultaneously the process of making E-Ktp. The type of research this research associative with the form of a causal relationship, a causal relationship a relationship that causal in nature, so here there are independent variables and dependent variables. data collection technique used was questionnaire submitted the respondents, namely the people who came take care of making E-KTP the Tebo Regency Population and Civil Registration Service and field documentation. The results showed that excellent service has a significant effect and has a positive direction towards the e-KTP making process with t_ (count) 4.184> t_ (table) 1.98609. Community satisfaction has a significant effect and has a positive direction towards the process of making e-ID card with t_ (count) 3.112> 〖t〗 _ (table) 1.98609. Excellent service and community satisfaction simultaneously (together) have significant effect on the e-ID card making process with F_count 26.328> F table 3.09. From the results of the coefficient of determination (R ^ 2), it is known that the contribution provided by excellent service and community satisfaction to employee performance is 36.4%, while the remaining 63.6% is influenced by other variables not examined in this study. The conclusion is that excellent service and community satisfaction have a partial and simultaneous effect on the e-ID card making process, because the value of t_ (count) 〖> t〗 _ (table.) And the value of F_count> F table and has a positive relationship direction.